(untitled) (Journal of Advanced Research in Social Sciences, 2022)
Race has been a prominent discourse in the contemporary world and academic discipline since the last few decades as it determines a variety of moral problems. In response to this discussion, race tends to emphasise a couple of philosophical aspects in favour of concepts and categories. The concept of race forms a debate in reality whilst racial taxonomy gives a physical system of division such as black, white, Asian, Native American, and so forth. Correspondingly, there have been remarkable problematic issues with regards to biological realism, antirealism or eliminativism alongside social constructivism. In addition, the particular term, race, predominantly embodies a pair of notions: it is a biological position, demarcated by observable physical characteristics in terms of certain ancestry and geographical territory - it is a historical moral perspective, which is construed by ancient societies. Therefore, by employing qualitative mode of enquiry, I attempt this research to defend the thesis that race is not real, and it could be an upshot of social constructivism. Then, I look forward to illuminating a few substantial findings: the central claims of antirealism or eliminativism, a critique of social constructivism along with a brief analysis of political and cultural constructionism. Notwithstanding these limited outcomes, this research suggests that further studies need to be carried out in order to explore the unreal nature of race.